A Comparative Study on the Effect of Metacognitive Regularities on the Work Efficiency of University Teachers across Public and Private Universities - Khadija Muhammad Hussain Marvi; Dr. Farkhanda Jabeen (Indus Journal of Social Sciences, 2025)
This study, a sub-part of a larger project on the effect of metacognitive regularities on university teachers’ work efficiency, compares public and private universities in Pakistan. It aims to enhance understanding of academic environments and support Pakistan’s 2030 educational goals. Quantitative data from 164 university teachers, collected via campus visits and online forms, revealed significant differences between the two sectors. Public university teachers scored higher in metacognitive regularities and work efficiency, demonstrating stronger planning, monitoring, and evaluation skills. The findings suggest that greater metacognitive regulation contributes to higher efficiency among public university teachers. The study recommends regular training, workshops, reflective journals, and peer review sessions to enhance teachers’ metacognitive regularities and pedagogical practices. Future research should investigate the factors behind public university teachers’ stronger metacognitive regularities and how university policies, training programs, and work environments effects metacognitive regularities and work efficiency.